THE SOURCES FOR FINANCING THE ACCOMODATION SUPPORT IN THE ARMED FORCES OF UKRAINE - Gorodianska, L.; Tsiukalo, L. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article presents the qualification of types of accommodation support in the Armed Forces of Ukraine (AFU) in accordance to which the military personnel and their family members are to be supported by newly built accommodation, liberated accommodation, acquired accommodation, service accommodation or a monetary compensation for a premise fit for living. The essence of the financial mechanism of accommodation support in the Armed Forces of Ukraine has been analyzed, which is basically comprised of the funds of the state budget according to the types of generic and special funds. It has been demonstrated that the existing financial mechanism is not perfect, limited in resources accompanied by a large number of bureaucratic obstacles, does not satisfy the modern request for accommodation support within the AFU. According to date provided at the 1-st of January 2021 the overall amount of military personnel accountable for accommodation is at 47,2 thousand, whilst at the same time in the years 2020 and 2021 at the costs of the budget it is only possible to build 4000 apartments a year, which is obviously not sufficient to meet the requirements of the Armed Forces of Ukraine as such. The main reason for the insufficient support of military personnel in terms of accommodation are the limited financial resources that are available to build or to buy (accommodation). Following the detailed analyses of the budget expenditures for the finance support in terms of the program of construction (acquiring) accommodation for military personnel in the years 2011-2020 it has been stipulated, that even the assets of the special fund have not been used completely in the course of the years 2011-2017 and the level of using the budget assets for the accommodation support within the AFU in an overall perspective was within the framework of 27-81 %. It has also been pointed out that the reason for the incomplete using of the budget assets is the systematic delay of approval of the passports of the budget approval of construction (acquiring) accommodation for servicemen. The article suggests the introduction of innovative approaches to support the military personnel with accommodation, namely mortgage lending, financial leasing and investment for housing construction on land plots of the Ministry of Defense of Ukraine. It is also suggested to implement the experience of NATO member state countries that happen to present service premises to military personnel situated on the territory of the unit (garrison) for temporary use, presenting monetary support to hire accommodation, interest-free loans or loans on preferential terms for the purchase or construction of accommodation.
Keywords: the sources of financing, budget expenditures, generic fund, special fund, accommodation support, construction (acquiring) of accommodation, premises fit for living